Missa solemnis - Beethoven, Ludwig van 1770-1827; Mozart, Wolfgang Amadeus 1756-1791; Mozart, Wolfgang Amadeus 1756-1791 (Testament, 1998)
Schwarzkopf samlingen.
Interpr.: Gundula Janowitz [Sopr]. Christa Ludwig [Alt].Fritz Wunderlich [Ten]. Walter Berry [Baß]. Singverein der Gesellschaft der Musikfreunde, Wien. Philharmonia Orchestra. Herbert von Karajan, Herbert [Dir.]. - Enth. außerdem: Symphony No. 38 in D, K. 504 "Prague" / Wolfgang Amadeus Mozart. Elisabeth Schwarzkopf talks about the recording. Rehearsal sessions for Missa Solemnis. - Aufn.: Wien, Musikvereinssaal, 12. - 17. 9.1958
Keywords: messe; symfoni